Local Wisdom-Based Environmental Management in the Traditional Village of Kuta, Ciamis Regency - Putri, Fina Alyani Imanda; Hilman, Iman; As’ari, Ruli (Prosiding Seminar Nasional Pendidikan, Ilmu-Ilmu Sosial, dan Hukum (SENPISHUM), 2026)
This study examines local wisdom-based environmental management in Kampung Adat Kuta, Ciamis Regency, which is still strongly embedded in the lives of the Sundanese indigenous community. Declining human concern for the environment has led to damage, so adapting local wisdom in the form of knowledge and norms passed down from generation to generation is a solution to maintain balance between humans and nature. A descriptive qualitative research method was used with data collection through observation, interviews, literature studies, and documentation. The results showed that local wisdom in Kampung Adat Kuta, such as rules on water use, agricultural land management rituals, environmentally friendly settlement arrangements, and preservation of sacred forests (leuweung gede), effectively maintained environmental sustainability and social harmony. This local wisdom is in line with the principles of sustainable development and supports the conservation of natural resources. In conclusion, local wisdom-based environmental management is an effective approach to maintaining environmental quality and the sustainability of natural resources in Kampung Adat Kuta.